2015
DOI: 10.1136/bcr-2014-208758
|View full text |Cite
|
Sign up to set email alerts
|

Iliacus haematoma causing femoral nerve palsy: an unusual trampolining injury

Abstract: We report the case of a 15-year-old boy who presented to accident and emergency following a trampolining injury. Initially, the patient was discharged, diagnosed with a soft tissue injury, but he re-presented 48 h later with worsening low back pain and neurological symptoms in the left leg. Subsequent MRI revealed a left iliacus haematoma causing a femoral nerve palsy. The patient was managed conservatively and by 6 months post injury all symptoms had resolved. This is the first reported case of an iliacus hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A traumatic iliacus hematoma is rare and usually occurs in patients after a fall involving a lower back injury 1 . The hematoma may compress the femoral nerve causing femoral nerve palsy, which results in severe pain and sensory disturbance along the distribution of the femoral nerve, and weakness or paralysis of the quadriceps muscle 1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A traumatic iliacus hematoma is rare and usually occurs in patients after a fall involving a lower back injury 1 . The hematoma may compress the femoral nerve causing femoral nerve palsy, which results in severe pain and sensory disturbance along the distribution of the femoral nerve, and weakness or paralysis of the quadriceps muscle 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A traumatic iliacus hematoma is rare and usually occurs in patients after a fall involving a lower back injury 1 . The hematoma may compress the femoral nerve causing femoral nerve palsy, which results in severe pain and sensory disturbance along the distribution of the femoral nerve, and weakness or paralysis of the quadriceps muscle 1 . To date, the gold standard treatment for this condition has not been established, and reports in the available literature describing femoral nerve palsy secondary to a traumatic iliacus hematoma recommend operative or conservative treatments 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subacute compartment syndrome resulting from pelvic trauma during contact sports can cause femoral nerve entrapment with progressive edema, swelling, and ischemia in the iliacus compartment. [26][27][28] With femoral nerve entrapment pain, numbness, and paresthesias may be noted in the anterior thigh and when the saphenous branch is involved symptoms may be noted in the anteromedial knee joint, medial leg, and foot. 4 In contrast, the lateral femoral cutaneous nerve is exclusively a sensory nerve with entrapment causing symptoms of paresthesia, numbness, stinging, or burning sensation in the anterior lateral thigh associated with hypersensitivity to touch.…”
Section: Anterior Nerve Entrapmentsmentioning
confidence: 99%
“…A recent systematic review identified only 16 cases of femoral neuropathy secondary to traumatic iliopsoas haematomas over a 40‐year period to 2012 . A reading of the cases reveals a trend towards conservative management of partial palsies and surgical decompression of complete palsies; however, it remains controversial when surgical intervention should be pursued over a conservative approach. The current authors freely admit that they were faced with a management uncertainty on initial presentation.…”
mentioning
confidence: 99%